Metabolic Potential for Reductive Acetogenesis and a Novel Energy-Converting [NiFe] Hydrogenase in Bathyarchaeia From Termite Guts – A Genome-Centric Analysis - Loh, Hui Qi; Hervé, Vincent; Brune, Andreas (Frontiers in Microbiology, 2021)
Symbiotic digestion of lignocellulose in the hindgut of higher termites is mediated by a diverse assemblage of bacteria and archaea. During a large-scale metagenomic study, we reconstructed 15 metagenome-assembled genomes of Bathyarchaeia that represent two distinct lineages in subgroup 6 (formerly MCG-6) unique to termite guts. One lineage (TB2; Candidatus Termitimicrobium) encodes all enzymes required for reductive acetogenesis from CO2 via an archaeal variant of the Wood–Ljungdahl pathway, involving tetrahydromethanopterin as C1 carrier and an (ADP-forming) acetyl-CoA synthase. This includes a novel 11-subunit hydrogenase, which possesses the genomic architecture of the respiratory Fpo-complex of other archaea but whose catalytic subunit is phylogenetically related to and shares the conserved [NiFe] cofactor-binding motif with [NiFe] hydrogenases of subgroup 4 g. We propose that this novel Fpo-like hydrogenase provides part of the reduced ferredoxin required for CO2 reduction and is driven by the electrochemical membrane potential generated from the ATP conserved by substrate-level phosphorylation; the other part may require the oxidation of organic electron donors, which would make members of TB2 mixotrophic acetogens. Members of the other lineage (TB1; Candidatus Termiticorpusculum) are definitely organotrophic because they consistently lack hydrogenases and/or methylene-tetrahydromethanopterin reductase, a key enzyme of the archaeal Wood–Ljungdahl pathway. Both lineages have the genomic capacity to reduce ferredoxin by oxidizing amino acids and might conduct methylotrophic acetogenesis using unidentified methylated compound(s). Our results indicate that Bathyarchaeia of subgroup 6 contribute to acetate formation in the guts of higher termites and substantiate the genomic evidence for reductive acetogenesis from organic substrates, possibly including methylated compounds, in other uncultured representatives of the phylum.